Development of a next-generation endogenous OCT4 inducer and its anti-aging effect in vivo - Han, Kang; Hasselbeck, Sebastian; Taškova, Katerina; Wang, Nessa; Oosten, Luuk N. van; Mrowka, Ralf; Utikal, Jochen; Andrade-Navarro, Miguel A.; Wang, Jichang; Wölfl, Stefan; Cheng, Xinlai (European journal of medicinal chemistry, 2023)
The identification of small molecules capable of replacing transcription factors has been a longstanding challenge in the generation of human chemically induced pluripotent stem cells (iPSCs). Recent studies have shown that ectopic expression of OCT4, one of the master pluripotency regulators, compromised the developmental potential of resulting iPSCs, This highlights the importance of finding endogenous OCT4 inducers for the generation of clinical-grade human iPSCs. Through a cell-based high throughput screen, we have discovered several new OCT4-inducing compounds (O4Is). In this work, we prepared metabolically stable analogues, including O4I4, which activate endogenous OCT4 and associated signaling pathways in various cell lines. By combining these with a transcription factor cocktail consisting of SOX2, KLF4, MYC, and LIN28 (referred to as "CSKML") we achieved to reprogram human fibroblasts into a stable and authentic pluripotent state without the need for exogenous OCT4. In Caenorhabditis elegans and Drosophila, O4I4 extends lifespan, suggesting the potential application of OCT4-inducing compounds in regenerative medicine and rejuvenation therapy.